A new mobile smartphone application, AF-EduApp, for atrial fibrillation patients: what do they use most?. Issue 4 (22nd December 2022) - Knaepen, L; Theunis, R; Delesie, M; Vijgen, J; Dendale, P; Desteghe, L; Heidbuchel, H
Abstract: Background: The management of atrial fibrillation (AF) is complex and based on three main pillars: avoid stroke, better symptom control and cardiovascular risk factor management. Therefore, a holistic, multidisciplinary approach is needed in which the patient has a central role. Smartphone ownership increases strongly in the elderly population (in Belgian 65+ years old: 52% in 2018 to 82% in 2020). This digital growth creates opportunities for a closer patient follow-up. An in-house developed application, AF-EduApp, focused on delivering targeted education and guiding self-care, has been validated and is currently being studied in an ongoing clinical trial. Purpose: Intermediate analysis of the user data of AF-EduApp. Methods: At two Belgian hospitals, an open, prospective, randomized trial is currently performed. A total of 153 AF patients hospitalized or seen at an out-patient visit were included. Patients could use the application during a follow-up of 12 months. The AF-EduApp consists of six different modules: education, questionnaires with immediate patient feedback, medication overview with reminders, measurements (e.g. blood pressure, heart rate), appointments, and the possibility to ask questions to the caregivers. Knowledge about AF and its treatment was tested through the Jessa Atrial fibrillation Knowledge Questionnaire (JAKQ) with feedback on incorrectly answered questions. The main aim of the AF-EduApp is to improve patients' medication adherence through improved education and medication reminders. Results: Currently, a total of 132 patients have completed a follow-up of 12 months (follow-up days: mean 357.3±60.7 and median: 365.5 [350.3–382.0]). The app was used on average 122.5±126.6 days (median: 55.0 [23.3–241.0]), or 34.3% of the available days. As shown in Fig. 1, the measurements and medication modules were the most used module (on 66.1% resp. 55.2% of the days). The education module was the least used module (3.5% of the days); the average education time was 17.0±27.7 min (median: 6.1 [1.4–20.6]). Within the measurement module (mean: 80.9±109.4 days used), the most frequently entered parameter was blood pressure, with on average 208.3±351.3 entries (median: 53.5 [7.0–296.3]) (Fig. 2). AF episodes was the least entered data (average 37.0±185.0 times; median 8.0 [4.0–19.0.3]). Conclusion: Patients actively engaged with an educational smartphone AF application on 1/3th of the available days. The measurement module was the most used (to enter health data) together with the medication module (to confirm intake after reminder). It shows that many patients appreciate the mHealth tool to "connect" with their condition. The clinical trial tries to answer whether such increasing interaction leads to improved self-management and outcomes. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The AF-EduApp study is supported by an BMS/Pfizer European Thrombosis Investigator Initiated Research Program (ERISTA) grant.